Herbal, Homeopathic and Hormonal Therapy Improves Macromineral Profile and Fertility Outcomes in Postpartum Anestrus Buffaloes - Kumar, A.; Kumar, R.; Kumar, R.; Srivastava, S.; Kumar, P.; Verma, H. (The Indian Journal of Animal Reproduction, 2021)
The study was aimed to assess the effect of Aegle marmelos (Indian Bael),  Oophorinum and Progesterone on serum calcium, phosphorus and fertility  outcomes. A total of 24 postpartum anestrous buffaloes were randomly allocated  in 4 groups as T0, T1, T2 and T3; each group comprised of six animals. All the  animals were dewormed with fenbendazole (10mg/kg) before commencement of  experiment. The T0 (untreated control) buffaloes were supplemented with mineral  mixture (50 gm daily for 10 days). In addition to mineral mixture, the T1, T2 and  T3 buffaloes were treated with Aegle marmelos, Oophorinum and progesterone  hormone, respectively. The serum calcium and phosphorus values was significantly  (P
Keywords: Aegle marmelos; Anestrus; Buffaloes; Herbal therapy; Homeopathy; Oophorinum